Answer:
The expression written by Emma to represent the amount of the money that Juan earned is WRONG.
Explanation:
Here, the amount earned by Juan by walking dogs = w
The amount earned byJuan lowing lawns = (2w - 6)
Now, the total amount earned by Juan
= Amount earned from (Mowing Lawn + Walking dogs)
= w + (2 w - 6)
On further simplification, we get:
w + (2 w - 6) = w + 2w - 6 = 3w-6 = 3(w-2)
So, the total amount earned by Juan = 3(w-2)
Now, the expression written by Emma = 2(3w-6)
and 2(3w-6) ≠ 3(w-2)
Hence, the expression written by Emma to represent the amount of the money that Juan earned is WRONG.